2003
DOI: 10.1053/jhep.2003.50036
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hepatitis B virus genotypes on the progression of chronic type B liver disease

Abstract: To investigate the hepatitis B virus (HBV) genotype-related differences in the progression of liver disease, 585 patients with chronic HBV infection including 258 with histologically verified chronic liver disease (CLD) and 74 with hepatocellular carcinoma (HCC) were examined. The mean ages of both patients with advanced fibrosis (F3 or F4) and with HCC were significantly older in genotype B than in genotype C patients (P ‫؍‬ .018, P ‫؍‬ .024, respectively). Both the hepatitis B e antigen (HBeAg) negativity ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
300
4
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(334 citation statements)
references
References 33 publications
27
300
4
3
Order By: Relevance
“…Consistent with an earlier study, 27 our patients with genotype C HBV infection also had higher hepatitis activity, including HAI scores, periportal inflammation, fibrosis scores, and scores excluding fibrosis. Although total HAI score in relapsers was significantly higher than that of sustained responders, none of these histologic scores was an independent factor of sustained response (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with an earlier study, 27 our patients with genotype C HBV infection also had higher hepatitis activity, including HAI scores, periportal inflammation, fibrosis scores, and scores excluding fibrosis. Although total HAI score in relapsers was significantly higher than that of sustained responders, none of these histologic scores was an independent factor of sustained response (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in accordance with the latter studies which showed the dominancy of genotype D on A. HBV genotypes have been shown to have a distinct geographic distribution. Genotypes B and C are prevalent in the East and South-East Asia [26]. In contrast, genotypes A and D are common in Western Europe and North America [19,24].…”
Section: Discussionmentioning
confidence: 99%
“…Differences between genotypes B and C in Asia [Kao et al, 2000;Orito et al, 2001;Tsubota et al, 2001;Chan et al, 2004;Yu et al, 2005] have not been reproduced, probably due to selection bias for the patients with severe disease [Sumi et al, 2003] or subgenotypes of B different between Japan (Bj) and Hong Kong (Ba) [Yuen et al, 2004]. Liver disease, once advanced beyond a certain severity, will progress spontaneously irrespective of HBV genotypes.…”
Section: Discussionmentioning
confidence: 99%